One Contract, Two Verdicts: A Comparative Analysis of Mudharabah Default Disputes in the Yogyakarta Religious Court - Syamsul Wathoni; Lalu Muhammad Salikurrahman; Khaerul Muttakin; Zulhaji Ismail; Hafisuddin Aritonang (Mafapress - Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA Pati, 2026)
This research is motivated by differences in judges' decisions in disputes over the default of a mudharabah contract in the religious court environment, even though the objects of the dispute and the legal bases used are similar. This study aims to analyze inconsistencies in judges' legal reasoning in assessing the elements of default and their implications for the consistency of the application of Sharia economic law in Indonesia. This research uses a qualitative method with a juridical-normative approach, drawing on two decisions of the Yogyakarta Religious Court, Number 392/Pdt.G/2021/PA. YK and Number 370/Pdt.G/2020/PA. YK by analyzing positive legal norms, DSN-MUI fatwas, and the principles of muamalah fiqh. The results of the study show that the judge in the first case emphasizes the legal-formal approach, oriented toward legal certainty, while the judge in the second case adopts a substantive-normative approach that considers the fairness and good faith of the parties. These paradigm differences indicate a disharmony in the interpretation of sharia law and in the proof of mudharabah contracts. This disharmony has implications for the weakening of legal certainty in the settlement of Sharia economic disputes. Theoretically, these findings confirm Gustav Radbruch's view of the tension between the value of legal certainty (rechtssicherheit) and substantive justice (gerechtigkeit) in judicial practice. Therefore, it is necessary to prepare guidelines for the interpretation of sharia economic law that integrates the principles of positive law, fiqh muamalah, and maqashid al-sharia in encouraging real business sector financing and supporting development of the sharia economy.